Есть ответ 👍

11 *(х-2)+3х=4*(х-8)-10 4х-(5х+8)=5-(12х-20) 24х=7*(2х-50) -7*(х+2)+3=-4*(х-6)-2 4х+(7-2х)*3=7-(12х-4) 6х-(2х-4)=10-(5х-15)

291
452
Посмотреть ответы 2

Ответы на вопрос:

миша741
4,8(63 оценок)

1)11*(х-2)+3х=4*(х-8)-10 11х-22+3х=4х-32-10 14х-22=4х-42 14х-4х=-42+22 10х=-20   /  : 10 х= -2 2) 4х-(5х+8)=5-(12х-20) 4х-5х-8=5-12х+20 -1х-8=25-12х -1х+12х=25+8 11х=33   / : 11 х=3 3)24х= 7*(2х-50) 24х= 14х-350 24х-14х=-350 10х=-350   / : 10 х= -35 4) -7*(х+2)+3=-4*(х-6)-2 -7х-14+3=-4х+24-2 -7х-11=-4х+22 -7х+4х=22+11-3х=33       / : 11х=-11 5) 4х+(7-2х)*3=7-(12х-4)4х+21-6х=7-12х+4-2х+21=11-12х-2х+12х=11-2110х=-10             / : 10х= -1 6 не получается
darya2401
4,6(67 оценок)

6*2,5=15

1,8*5=9

0,75*4=3

Пошаговое объяснение:

это правильно

Популярно: Математика